Theoretical Analysis of Ors Tools on Geographic Information Systems for Mapping Historical Tourism Area in The City of Banjarmasin - Muhaimin, Muhammad (Media Wisata, 2023)
The research objectives include developing an isochrones computational model for historical site tourism in Banjarmasin City, analyzing isochrones computational modelling in mapping the fastest and shortest routes for historical site tourism in Banjarmasin City, and analyzing isochrones computational modelling to determine the distance-time matrix for historical site tourism in Banjarmasin City. Data analysis techniques to produce research objectives include analysis of historical sites in Banjarmasin City which is used to calculate the position of historical sites relative to other historical sites to analyze the best tourist routes for historical sites in Banjarmasin City. The research results confirm that the isochrones computing model can use a Geographic Information System (GIS) with QGIS and GraphHopper software for historical site tourism in Banjarmasin City.